The relationship between obstructive sleep apnea, dyspnea, and health-related quality of life in lung cancer survivors: a cross-sectional study in the Republic of Korea - Hyeong-pyo Kim; Duck-won Oh; Dong-kyu Kim (Osong Public Health and Research Perspectives)
Objectives The purpose of this study was to explore the relationships among obstructive sleep apnea (OSA), dyspnea, and health-related quality of life (HRQOL), as well as the factors influencing HRQOL. Methods A total of 129 lung cancer survivors (mean age, 53.4 years; 77 men and 52 women; mean time since diagnosis, 1.6 years; and cancer stage [1/2/3/4/relapse], 43/31/19/34/2, respectively) completed a questionnaire that included demographic and clinical information, as well as questions about the severity of sleep apnea, dyspnea, and HRQOL. The severity of OSA, dyspnea, and HRQOL were assessed using the Berlin questionnaire, the Dyspnea-10 item (FACIT-Dyspnea), and the European Organization for Research and Treatment of Cancer QLQ-C30, respectively. Results The severity of OSA and dyspnea exhibited negative correlations with HRQOL (p<0.05). Multiple regression analysis revealed that several factors significantly impacted the HRQOL of lung cancer survivors. These included the extent of dyspnea (β=−0.369, p<0.01), weight loss (β=0.192, p<0.01), OSA score (β=−0.215, p<0.01), stage 2 cancer (β=−0.181, p<0.01), and poor perceived health status (β=−0.179, p<0.05). Conclusion These findings suggest that breathing difficulties, including OSA and dyspnea, contribute to decreased HRQOL. This study offers valuable insights for researchers and clinicians, aiding in the development of effective strategies to manage these issues in daily life.